2019
DOI: 10.3390/ijerph17010246
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Site-Specific Cancer in People with Type 2 Diabetes: A National Cohort Study

Abstract: A retrospective cohort design was used with the objective to evaluate cancer risk among people with type 2 diabetes mellitus (T2DM) in Lithuania. The cohort was established by identifying all patients with the first diagnosis of T2DM in the National Health Insurance Fund database during 2000-2012. Cancer cases were identified by record linkage with the Lithuanian Cancer Registry. Standardized incidence ratios (SIRs) were calculated. Of the 127,290 people that were included, 5959 cases of cancer in men and 6661… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
2
21
1
Order By: Relevance
“…Furthermore, our study showed that both men and women with diabetes had not only an increased risk of death from diabetes itself and from CVD, but substantially higher mortality risk from infectious, digestive, and genitourinary diseases. The mortality risk due to cancer, however, was significantly elevated only for women with diabetes, probably because of increased corpus uteri and breast cancer risk that we have found in Lithuanian diabetic women [10]. Even more, increased risk for mortality from respiratory diseases was also seen in diabetic women.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Furthermore, our study showed that both men and women with diabetes had not only an increased risk of death from diabetes itself and from CVD, but substantially higher mortality risk from infectious, digestive, and genitourinary diseases. The mortality risk due to cancer, however, was significantly elevated only for women with diabetes, probably because of increased corpus uteri and breast cancer risk that we have found in Lithuanian diabetic women [10]. Even more, increased risk for mortality from respiratory diseases was also seen in diabetic women.…”
Section: Discussioncontrasting
confidence: 46%
“…Furthermore, diabetes has been associated with an increased risk for some types of site- specific cancer [ 9 ]. In fact, we recently found that T2DM is associated with increased risk for pancreas, liver, kidney, and thyroid cancer in men and women and breast and corpus uteri in women in the Lithuanian population [ 10 ]. Whether cancer increases mortality in people with T2DM in Lithuania is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating lines of evidence have demonstrated that DM is associated with greater risk of certain types of cancer at multiple sites, such as pancreatic, liver and endometrium cancer. 15–20 Nonetheless, the relationship between DM and the observed excess risk of cancer may be a result of confounding factors such as age, obesity, physical activity and exogenous insulin therapy. 15 21 22 …”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle habits of smoking or drinking and lifestyle-related diseases, such as diabetes mellitus (DM) or hypertension are considered to risk factors for various types of cancer [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Cigarette smoking is reported to be a major risk factor for head and neck, lung, and esophageal cancer through the exposure of the respiratory system and upper digestive tract to carcinogens [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption is also associated with the development of liver, breast, upper-aerodigestive tract, and head and neck cancer through ethanol-mediated carcinogenesis in metabolic disorders or immunosuppressive effects [8,9]. DM patients have a signi cantly increased risk of liver, pancreas, and kidney cancer due to exposure to multiple molecules that are expanded by metabolic abnormalities [10][11][12]. Obesity is de ned by an elevated body mass index (BMI) as a consequence of excessive adipose tissue.…”
Section: Introductionmentioning
confidence: 99%